Correctly select the steps to solve the given equation. 3x−7−2x+5=6 *Remember to include the correct optional first step.* (1 point

1 answer

To solve the equation \(3x - 7 - 2x + 5 = 6\), you can follow these steps:

  1. Optional First Step: Combine like terms on the left side of the equation.

    • \(3x - 2x - 7 + 5 = 6\)
  2. Combine the \(x\) terms and the constants:

    • \( (3x - 2x) + (-7 + 5) = 6\)
    • \(x - 2 = 6\)
  3. Add 2 to both sides of the equation to isolate the variable:

    • \(x - 2 + 2 = 6 + 2\)
    • \(x = 8\)

So, the solution is \(x = 8\).

Similar Questions
  1. Drag and drop the correct steps to solve the equation for x.Make sure to put the steps in order. Not all steps listed will be
    1. answers icon 1 answer
  2. Consider this equation:4(3x−2)=−24 4 ( 3 𝑥 − 2 ) = − 24 Correctly order the steps used to solve this equation. (1
    1. answers icon 1 answer
  3. 1 of 81 of 8 ItemsQuestion 1 Consider this equation: 4(3x−2)=−24 Correctly order the steps used to solve this equation. (1
    1. answers icon 11 answers
    1. answers icon 2 answers
more similar questions